Diallel analysis for yield and component traits in maize (Zea mays) under infestation and non-infestation with pink stem borer (Sesamia cretica) - ISMAIL, MOHAMMAD REDA; EL-HOSARY, ALI A; EL-BADAWY, MAHMOUD EL M; ABDALLAH, TAMER A E (The Indian Journal of Agricultural Sciences, 2019)
A half diallel cross between nine yellow inbred lines of maize (Zea mays L.) was evaluated under two environments, viz. borer artificial infestation conditions and normal conditions in RCBD with three replications in 2015 to estimate general and specific combining ability effects and identify superior genotypes resistant to Sesamia cretica. Highly significant cross mean squares were detected for all the studied traits indicating the wide diversity in the parental materials used in this study. General and specific combining ability (GCA and SCA) were significant for all the studied traits except SCA for number of rows/ear in normal condition revealing that both additive and non-additive gene effects were involved in determining the performance of the single cross progeny. The parental inbred line P6, P8 and P9 can be considered as good combiners for grain yield and some of its component traits under infestation and non-infestation conditions as well as the combined over them. Six crosses (P1×P6, P1×P7, P2×P4, P3×P5, P5×P7, and P8×P9) selected based on desirable SCA effects also had high mean performance for grain yield and out-yielded the check hybrid SC 166. Therefore, these crosses could be utilized for future breeding work as well as for direct release after confirming the stability of their performance across different environments. The information from this study may be useful for researchers who would like to develop high yielding hybrids of maize tolerant to borer attack.